Influence of genetic factors on neurophysiological mechanisms of neurodegenerative diseases - Natalia V. Ponomareva; Vitaliy F. Fokin; Evgeny I. Rogaev; Sergey N. Illarioshkin (Анналы клинической и экспериментальной неврологии, 2018)
The review summarizes the main results of studies on the influence of genetic factors on neurophysiological changes in neurodegenerative age-related diseases Alzheimer's (AD), Parkinson's (PD) and Huntington (HD) diseases. In some cases, neurophysiological methods make it possible to detect early changes already at the preclinical stage of neurodegenerative process. Such neurophysiological markers may be considered as endophenotypes and used for the early diagnosis of the diseases. The conducted studies are promising for clarifying which factors underlie the heterogeneity of diseases not only at the genetic level, but also at the neurophysiological level. At the same time, such an approach showed the presence of a number of neurophysiological alterations common to AD, PD, and HD. Disconnection of neural circuits, including interhemispheric disintegration, slowdown of information processes, disinhibition, hyperexcitability and epileptogenesis, as well as alterations in neurovascular coupling, are of great importance for the development of diseases. On the other hand, neurophysiological changes can directly affect the development of the disease, including the genetic level, as evidenced by experimental optogenetic studies, the results of deep brain stimulation and other neuromodulation methods. These data are valuable for a personalized approach to the prevention and treatment of age-dependent neurodegenerative diseases.